Casein-assisted biomineralization of calcium carbonate microspheres for enhanced surface and adsorption properties - Gade, Aniket; Nadrowska, Julia; Trzcińska-Wencel, Joanna; Wiśniewski, Marek; Raut, Rajesh; Rai, Mahendra; Golińska, Patrycja (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionBiomineralization is a key biological process by which organisms form mineralized structures, with calcium carbonate being one of the most abundant naturally occurring biominerals. The development of synthetic analogs, particularly calcium carbonate microspheres (CaCO3-MS), holds potential for various applications, including as carrier materials.MethodsIn this study, CaCO3-MS were synthesized using a precipitation method, both with and without casein. Ammonium, sodium, and potassium carbonate were evaluated as precipitating agents to optimize microsphere formation. The physical properties of the resulting microspheres were characterized using nitrogen adsorption analysis, Brunauer-Emmett-Teller (BET) analysis, diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) analysis.ResultsAmmonium carbonate was the most effective precipitating agent, yielding well-formed microspheres. Casein-assisted CaCO3-MS exhibited a higher specific surface area (65 m2/g) than CaCO3-MS synthesized without casein (47 m2/g). The casein-containing microspheres also demonstrated a more uniform spherical morphology, increased pore volume, higher surface energy, enhanced hydrophilicity, and approximately double the water adsorption capacity. However, both variants showed similar adsorption-desorption kinetics.DiscussionThe presence of casein significantly improved the structural and functional properties of CaCO3-MS, making them more suitable for use as carrier materials. Furthermore, the described method enables the large-scale, surfactant-free synthesis of uniformly sized microspheres, enhancing its practical applicability.